Melatih Literasi Pada Anak Usia Golden Age Melalui Mendongeng - Azizah Azizah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
Early childhood literacy is a crucial foundation for child development, playing a key role in shaping language skills, imagination, and understanding of the world. Storytelling has been widely recognized as an effective tool for fostering literacy in preschool children. This article investigates the effectiveness and benefits of storytelling in enhancing the literacy skills of 0-6-year-old children. By exploring psychological theories and related research, we can understand how storytelling influences children's cognitive and language development. Furthermore, this article discusses practical strategies for parents, teachers, and caregivers in effectively utilizing storytelling to enrich children's literacy experiences. It is hoped that the results of this study will provide readers with valuable insights into the importance of storytelling as a crucial tool in fostering literacy in preschool children.